Penyusunan Artikel Hasil Penelitian: Workshop Bagi Guru Sman 1 Dawarblandong Mojokerto - Moh. Syukron Maftuh; Sri Rahayu; Lydia Lia Prayitno; Silviana Maya Purwasih; Sri Rahmawati Fitriatien (Universitas PGRI Adi Buana Surabaya, 2021)
The preparation of research articles is an obligation of high school teachers as an effort to support their careers. However, many of the teachers of SMAN 1 Dawarblandong have experienced difficulties in compiling articles. This community service uses workshops. The participants are teachers of SMAN 1 Dawarblandong. This activity will be divided into two stages, namely the initial stage starting with the dissemination of the delivery of the definition of scientific articles and the importance of writing scientific articles and the second stage of a workshop on assisting the preparation of scientific articles based on research results. From these activities, it was found that teachers were more familiar with the basic concepts of scientific articles and were able to compile scientific articles of research results well.